(untitled)
Hkkjrh; x.kra= dh foxr yxHkx N% n’kdksa esa yksdrkaf=d izfØ;k dsdk;Zdj.k us Hkkjr esa fuokZpu ra= dh lkerk dh vko’;drk dks js[kkafdr rks fd;kgh] lkFk gh bl ckr dk Hkh izek.k izLrqr fd;k Fkk fd Hkkjr esa fuokZpu ra=lkekU;r% fuokZpu izfØ;k ds lqpk: vkSj lqnk fuoZgu esa lke fl) gqvk gSA, number=10, journal=Journal of Advances and Scholarly Researches in Allied Education, year=2013, month=Apr., pages=0–0